2021
DOI: 10.1093/gbe/evab128
|View full text |Cite
|
Sign up to set email alerts
|

The Dryas iulia Genome Supports Multiple Gains of a W Chromosome from a B Chromosome in Butterflies

Abstract: In butterflies and moths, which exhibit highly variable sex determination mechanisms, the homogametic Z chromosome is deeply conserved and is featured in many genome assemblies. The evolution and origin of the female W sex chromosome, however, remains mostly unknown. Previous studies have proposed that a ZZ/Z0 sex determination system is ancestral to Lepidoptera, and that W chromosomes may originate from sex-linked B chromosomes. Here, we sequence and assemble the female Dryas iulia genome into 32 highly conti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
58
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(63 citation statements)
references
References 71 publications
3
58
2
Order By: Relevance
“…However, a possibility that at least in Tischeriidae W chromosome evolved from the fusion of a Z chromosome and an autosome has not been ruled out ( Dalíková et al, 2017 ; Hejníčková et al, 2019 ). Recent data from genome sequencing in another butterfly species Dryas iulia (tribe Heliconiini) support the origin of a W sex chromosome from a B chromosome and suggest that this event may have happened multiple times during the evolution of butterflies ( Lewis et al, 2021 ). It has also been proposed that the ancestral Y chromosome in Drosophila may have originated from a B chromosome ( Hackstein et al, 1996 ; Carvalho, 2002 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, a possibility that at least in Tischeriidae W chromosome evolved from the fusion of a Z chromosome and an autosome has not been ruled out ( Dalíková et al, 2017 ; Hejníčková et al, 2019 ). Recent data from genome sequencing in another butterfly species Dryas iulia (tribe Heliconiini) support the origin of a W sex chromosome from a B chromosome and suggest that this event may have happened multiple times during the evolution of butterflies ( Lewis et al, 2021 ). It has also been proposed that the ancestral Y chromosome in Drosophila may have originated from a B chromosome ( Hackstein et al, 1996 ; Carvalho, 2002 ).…”
Section: Introductionmentioning
confidence: 99%
“…Based on these findings, it has been proposed that the effects of B chromosomes on their host may shift back and forth from parasitic or neutral to beneficial ( Camacho et al, 2000 ). In some species, it has been even hypothesised that B chromosomes may became an essential, stable part of the genome turning, for example, into new sex chromosomes or chromosomes restricted to germline that became essential for viability and fertility of their carriers ( Carvalho, 2002 ; Nokkala et al, 2003 ; Dalíková et al, 2017 ; Torgasheva et al, 2019 ; Imarazene et al, 2021 ; Lewis et al, 2021 ). In this review we describe mechanisms of B chromosome origin, strategies of their inheritance and give examples of the “cellular domestication” of B chromosomes, where these chromosomes provide some important functions for their hosts.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While having a size equal to an average autosome, the W-chromosome demonstrated very specific features; both a significantly higher overall proportion of TEs, a larger fraction of longer TEs, and a different distribution of repeat classes compared to other chromosomes. Similar to the silkmoth and julia heliconian (Dryas iulia), the W-chromosome in the painted lady had a significantly higher proportion of LTRs and LINEs (Lewis et al, 2021;Mita et al, 2004). The proportion of SINEs was however much smaller on the W-chromosome than on the autosomes and the Zchromosome.…”
Section: Global and Chromosome Specific Recombination Ratesmentioning
confidence: 93%
“…However, the authors found that these mobile elements were not restricted to the W chromosome and that they exhibited stage-, sex-, pairing-, gonad-, and strain-specific transcription. As explained in the Highlight feature on this article ( McGrath 2021a ), the authors hypothesize that W elements “not only influence the biology of S. mansoni , but they might represent one of the sources of heritable variability, thus shaping the evolution of the family Schistosomatidae.” In another study of W chromosome repeats, Stephen H. Montgomery and coauthors describe the W chromosome in the butterfly Dryas iulia , which exhibits female-specific gene expression and chromatin accessibility and is characterized by highly repetitive DNA content ( Lewis et al 2021 ). Their findings suggest that the evolution of the W chromosome in this species may have been heavily driven by repetitive elements and that these elements may have originated from a B chromosome, a nonessential chromosome with variable presence within populations.…”
mentioning
confidence: 99%